2021
DOI: 10.1111/jbi.14065
|View full text |Cite
|
Sign up to set email alerts
|

Recent divergence and lack of shared phylogeographic history characterize the diversification of neotropical savanna birds

Abstract: Aim: Neotropical savanna birds occur north and south of, but mostly not in the Amazon Basin, except for a few isolated savanna patches. Here, we investigate the phylogeography of 23 taxa of Neotropical savanna birds co-distributed across multiple isolated savanna patches to assess to what extent these species have a shared history of spatial diversification. We explore the role of the forested Amazon Basin as a vicariant barrier separating northern and southern populations, particularly focusing on the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 71 publications
3
5
2
Order By: Relevance
“…A lack of consensus in intraspecific tree topologies of organisms shared between the Cerrado and the Amazonian savannas is in accordance with a previous study (van Els et al, 2021), which supported multiple origins of the isolated Amazonian savannas as well as of the Cerrado populations. For some plant species, genomic and chloroplast DNA data suggest colonization of Amazonian savannas from the Cerrado about 149,000 years ago (Buzatti et al, 2018), whereas in other organisms divergence between the savannas to the north and south of the Amazon River pre‐dates the LIG (Buzatti et al, 2018; Resende‐Moreira et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A lack of consensus in intraspecific tree topologies of organisms shared between the Cerrado and the Amazonian savannas is in accordance with a previous study (van Els et al, 2021), which supported multiple origins of the isolated Amazonian savannas as well as of the Cerrado populations. For some plant species, genomic and chloroplast DNA data suggest colonization of Amazonian savannas from the Cerrado about 149,000 years ago (Buzatti et al, 2018), whereas in other organisms divergence between the savannas to the north and south of the Amazon River pre‐dates the LIG (Buzatti et al, 2018; Resende‐Moreira et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…angustirostris is one exception (Kopuchian et al, 2020; Rocha et al, 2020). These studies rejecting isolation by distance in Cerrado birds differ from our study with respect to the different geographic scale of the study area (e.g., Luna et al, 2017), and in the use of different genetic markers (e.g., van Els et al, 2021; Lima‐Rezende et al, 2019; Luna et al, 2017; Savit & Bates, 2015). It is becoming commonly accepted that multilocus studies are more suitable than single‐locus studies to evaluate population genetic structure and evolutionary phenomena such as isolation by distance (Teske et al, 2018).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Similarly, across many Central American bird species, diet—but not habitat—was a better predictor of dispersal ability (Miller et al, 2021), with species that track ephemeral food resources having greater dispersal ability and lower population structure. In contrast, habitat preference was associated with the amount of population genetic structure (Bates et al, 2003; van Els et al, 2021). In Amazonian birds, Harvey et al (2017) found greater genetic structure in upland forest species than in floodplain forest species, and Barbosa et al (2022) found differences in structure between species in distinct habitats within Amazonian floodplains.…”
Section: Introductionmentioning
confidence: 99%
“…Several Leistes specimens from Pando at the Louisiana State University Museum of Natural Science, Baton Rouge (LSUMZ) were identified as L. superciliaris based on phenotype. However, some have the mitochondrial DNA of militaris (van Els et al . 2021, in prep.…”
Section: Species Accountsmentioning
confidence: 99%